ANALISIS DAN PERANCANGAN SISTEM PENUNJANG KEPUTUSAN PEMILIHAN GURU BERPRESTASI DENGAN MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGTING (SAW) PADA SMK N 1 MUARO JAMBI - Fauziah, Yunarni; Sarjono, Sarjono (Jurnal Manajemen Sistem Informasi, 2016)
The research aims to develop decision support system. Thus it ease the process of selecting outstanding teachers and provide an alternative selection of grade system to selecting outstanding teachers. This decision support system use the calculation method of Simple Additive weighting (SAW). This system can demonstrate the results of grade system for outstanding teachers, based on the calculation method of SAW. However, in the SAW method has not been able to resolve a case in which there yag same preference value. Thus, in this system added an algorithm to resolve the case by comparing the values in each criteria. The criteria used in this study is the educational qualifications, tenure, value SKP, self-development and decision support prestasi.Sistem selecting outstanding teachers with SAW method can help facilitate the election of outstanding teachers and provides an alternative method results perangkingan SAW. Future studies are recommended to develop a decision support system for the selection of outstanding teachers by using a different method or combination of methods SAW with other methods.